Ending a bad start: Triggers and mechanisms of co-translational protein degradation - Eisenack, Tom Joshua; Trentini, Débora Broch (Frontiers in Molecular Biosciences, 2023)
Proteins are versatile molecular machines that control and execute virtually all cellular processes. They are synthesized in a multilayered process requiring transfer of information from DNA to RNA and finally into polypeptide, with many opportunities for error. In addition, nascent proteins must successfully navigate a complex folding-energy landscape, in which their functional native state represents one of many possible outcomes. Consequently, newly synthesized proteins are at increased risk of misfolding and toxic aggregation. To maintain proteostasis – the state of proteome balance – cells employ a plethora of molecular chaperones that guide proteins along a productive folding pathway and quality control factors that direct misfolded species for degradation. Achieving the correct balance between folding and degradation therefore represents a fundamental task for the proteostasis network. While many chaperones act co-translationally, protein quality control is generally considered to be a post-translational process, as the majority of proteins will only achieve their final native state once translation is completed. Nevertheless, it has been observed that proteins can be ubiquitinated during synthesis. The extent and the relevance of co-translational protein degradation, as well as the underlying molecular mechanisms, remain areas of open investigation. Recent studies made seminal advances in elucidating ribosome-associated quality control processes, and how their loss of function can lead to proteostasis failure and disease. Here, we discuss current understanding of the situations leading to the marking of nascent proteins for degradation before synthesis is completed, and the emerging quality controls pathways engaged in this task in eukaryotic cells. We also highlight the methods used to study co-translational quality control.